Analysis of Students' Errors in Solving Statistical Problems: A Case of 8th Grade Students at SMPN 4 Siak Hulu, Indonesia - Suripah, Suripah; Mayani, Inggi; Muhammad, Ilham (FKIP Universitas Lampung, 2022)
The purpose of this research is to describe and analyze the mistakes made by students when working on math problems in statistics material. This research was conducted in class VIII SMPN 4 Siak Hulu, with 10 students as research subjects. This type of research is a qualitative descriptive research. Data collection techniques are using tests, and unstructured interviews. The results showed that: 1) there were 4 types of errors, namely conceptual errors by 30%, fact errors by 4%, procedural errors by 14%, and technical errors by 10%; 2) there are 5 indicators discussed related to statistical material, namely indicator 1 (Determining the average value of a data), indicator 2 (Analyzing data), indicator 3 (Determining the median of even data), indicator 4 (Determining the mode value of a data), indicator 5 (Determining the values of the first, second and third quartiles in group data). In the fifth indicator, only 3 out of 10 students were able to answer correctly or 30%, this is the indicator with the lowest percentage of the five indicators; 3) the cause of student errors is the lack of student understanding of the prerequisite material for that solution in order to overcome similar errors, namely by always checking student understanding regarding prerequisite material before starting the lesson and choosing appropriate learning methods and strategies so that students can easily understand the material being taught.. Keywords: students’ error analysis, statistics learning, junior high school students. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp1827-1838